2007
DOI: 10.1111/j.1365-2133.2007.08362.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an enhanced proteomic method to detect prognostic and diagnostic markers of healing in chronic wound fluid

Abstract: Results obtained indicate that this approach significantly improves separation of proteins present in low concentrations in CWF. This will facilitate the identification of biomarkers in samples collected from patients with ulcers and lead to improved patient therapies and wound care approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 45 publications
0
46
0
1
Order By: Relevance
“…We refer you to a number of recent microarray studies that provide transcriptional information about specific aspects of the process. On the basis of these publications, as well as the first reported proteomic analyses of wound exudates (Fernandez et al, 2008;Huang et al, 2006), it is evident that the wound milieu contains many potentially novel proteins that influence wound repair. Studies using transgenic and knockout mice, as well as other strategies such as topical treatment of wounds with ligands and/or inhibitors, have already confirmed that a plethora of factors influence the migration and proliferation of epidermal and dermal cells, and wound contraction.…”
Section: Resultsmentioning
confidence: 99%
“…We refer you to a number of recent microarray studies that provide transcriptional information about specific aspects of the process. On the basis of these publications, as well as the first reported proteomic analyses of wound exudates (Fernandez et al, 2008;Huang et al, 2006), it is evident that the wound milieu contains many potentially novel proteins that influence wound repair. Studies using transgenic and knockout mice, as well as other strategies such as topical treatment of wounds with ligands and/or inhibitors, have already confirmed that a plethora of factors influence the migration and proliferation of epidermal and dermal cells, and wound contraction.…”
Section: Resultsmentioning
confidence: 99%
“…Burn patient serum has been investigated for biomarkers predicting survival in severely burnt patients [9]; but as the incidence of burn mortality in Australia is relatively low, the majority of paediatric patients presenting to Australian burn centres do not face these survival concerns [10,11]. Studies focussing on biomarkers that could assist in predicting cutaneous wound healing trajectories have predominantly been conducted with the aim of assessing chronic non-healing wounds rather than acute wounds [12][13][14][15]. Although burn wound exudate has been used as a healing wound comparator in some chronic wound focussed studies [16,17], it is unclear whether a similar approach could be applied when assessing acute burn wounds only.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case for wound exudates, which can be either directly collected from the wound site (33,34) or extracted from wound dressings (35). Several proteomic analyses of wound fluids have been performed that mostly focused on the quantitative comparison of proteins in fluids from normal and impaired healing (33,35).…”
mentioning
confidence: 99%